1995
DOI: 10.1074/jbc.270.7.3216
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinate Adenine Dinucleotide Phosphate (NAADP) Triggers a Specific Calcium Release System in Sea Urchin Eggs

Abstract: Transient fluxes of intracellular ionized calcium (Ca2+) from intracellular stores are integral components of regulatory signaling pathways operating in numerous biological regulations, including in early stages of egg fertilization. Therefore, we explored whether NADP, which is rapidly generated by phosphorylation of NAD upon fertilization may, directly or indirectly, exert a regulatory role as a trigger of Ca2+ release from intracellular stores in sea urchin eggs. NADP had no effect, but we found that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 17 publications
7
142
0
Order By: Relevance
“…Unlike cADPR-and InsP 3 -mediated Ca 2+ release, NAADP-induced Ca 2+ release is insensitive to changes in cytosolic Ca 2+ concentration or Ca 2+ chelation, indicating that the target receptor for NAADP is not subject to Ca 2+ -induced Ca 2+ -release (CICR) (Chini and Dousa 1996). In urchin egg homogenates, NAADP-evoked Ca 2+ release is not affected by blockers of cADPRor IP 3 -induced Ca 2+ release, 8-NH 2 -cADPR or heparin (Lee and Aarhus 1995), ER Ca 2+ depletion by thapsigargin (Genazzani et al, 1996), or prior Ca 2+ release by cADPR or IP 3 (Chini et al, 1995), but is desensitised by prior NAADP-induced Ca 2+ release (Lee and Aarhus 1995). In addition, prior exposure to non-Ca 2+ -releasing concentrations of NAADP has been shown to desensitise urchin egg homogenates to subsequent release by activating concentrations (Genazzani et al, 1996).…”
Section: Acidic Endolysosomal Ca 2+ Stores and Naadpmentioning
confidence: 94%
“…Unlike cADPR-and InsP 3 -mediated Ca 2+ release, NAADP-induced Ca 2+ release is insensitive to changes in cytosolic Ca 2+ concentration or Ca 2+ chelation, indicating that the target receptor for NAADP is not subject to Ca 2+ -induced Ca 2+ -release (CICR) (Chini and Dousa 1996). In urchin egg homogenates, NAADP-evoked Ca 2+ release is not affected by blockers of cADPRor IP 3 -induced Ca 2+ release, 8-NH 2 -cADPR or heparin (Lee and Aarhus 1995), ER Ca 2+ depletion by thapsigargin (Genazzani et al, 1996), or prior Ca 2+ release by cADPR or IP 3 (Chini et al, 1995), but is desensitised by prior NAADP-induced Ca 2+ release (Lee and Aarhus 1995). In addition, prior exposure to non-Ca 2+ -releasing concentrations of NAADP has been shown to desensitise urchin egg homogenates to subsequent release by activating concentrations (Genazzani et al, 1996).…”
Section: Acidic Endolysosomal Ca 2+ Stores and Naadpmentioning
confidence: 94%
“…Separation of sea urchin microsomes on Percoll gradients has demonstrated that the InsP 3 -and cADPR-dependent Ca 2ϩ release pathways coreside in the same fraction, whereas the NAADPsensitive vesicles are scattered throughout various fractions (39). However, the precise membrane location of the NAADPsensitive Ca 2ϩ pool could not be defined (12,50). It is interesting to note that the distribution of ligand-sensitive Ca 2ϩ pools share similar patterns in both sea urchins and plants, whereby InsP 3 -and cADPR-gated channels coreside on the same membrane type, ER in the case of sea urchins and the vacuolar membrane in the case of plants.…”
Section: Discussionmentioning
confidence: 99%
“…The two Ca 2ϩ -mobilizing agents cADPR and NAADP, although structurally related (36) and produced by the same ADP-ribosyl cyclase activity (37), trigger Ca 2ϩ release through independent mechanisms in sea urchin eggs (9,12). To ascertain whether the NAADP-dependent Ca 2ϩ release pathway is distinct from that activated by cADPR in plant cells, Ca 2ϩ -loaded beet microsomes were treated with saturating doses (1 M) of cADPR and subsequently NAADP.…”
Section: Naadp-induced Camentioning
confidence: 99%
See 1 more Smart Citation
“…NAADP ϩ releases Ca 2ϩ via a mechanism distinct from those triggered by Ins-P 3 and cADPr because: (i) the antagonists heparin and 8-NH 2 -cADPr do not block NAADP ϩ -induced Ca 2ϩ release (4); (ii) desensitization of Ins-P 3 and ryanodine receptors does not influence NAADP ϩ -induced Ca 2ϩ release (4,5); and, (iii) NAADP ϩ -induced Ca 2ϩ release appears to be additive to that induced by Ins-P 3 or cADPr. (7).…”
Section: Mobilization In Both Immature Oocytes and In Oocytes Maturedmentioning
confidence: 99%